The study of the ultrasonic method of applying of emitter on the electrodes of gas-discharge lamps - Кузнецова, Т. Ю.; Ківа, О. В.; Грибініченко, В. В. (Scientific Progress & Innovations, 2016)
We have developed a method of applying of emitter on the electrodes of gas-discharge lamps, which differs that before and during immersion and exposition of electrodes in suspension the last one is irradiated by ultrasound which is turned off before electrodes would be taken out from suspension. We have conducted experimental researches on the electrodes of DRL-250 lamps concerning influencing an ultrasound on the increase of emitter mass which is inflicted on an electrode, and on the degree of filling of internal cavities of electrode by emitter. On the basis of these researches we suggested a technology of the ultrasonic applying of emitter on the electrodes of gas-discharge lamps. In the article the results of the conducted experimental tests and comparative descriptions are given for the methods of applying of emitter on the electrodes of gas-discharge lamps using the known technology and using ultrasound.